Curriculum Organization for Elementary School Mathematics Learning to Optimize The Potential (Fitrah) of Learners - Nasywa Hilmi; Andi Prastowo (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Phobia in learning mathematics is one of the factors that influences the high school dropout rate among elementary school children. Curriculum organization is intended to encourage students in learning to be able to develop according to their interests, talents, potential and natural needs. The aim of this research is to collect and analyze the phenomenon of proper curriculum organization in elementary school mathematics learning to optimize students' potential. The research approach used is qualitative. With field research at Islamic elementary schools in Sleman Regency, Special Region of Yogyakarta. This research shows that the implementation of the mathematics learning curriculum in international Islamic elementary schools aims to integrate Islamic values ​​in learning, focus on developing critical and creative thinking skills, and optimize student potential through subject integration. The positive impacts include a more comprehensive understanding of mathematical concepts and the development of students' natural potential. However, constraints such as limited time and research scope, as well as potential data limitations due to not using quantitative methods, need to be considered for more effective research and implementation in the future.